An Experimental Study on the Microstructures of Cemented Paste Backfill during Its Developing Process - Bo Zhang; Jie Xin; Lang Liu; Lijie Guo; Ki-Il Song (Advances in Civil Engineering)
The aim of this study was to examine the microstructure of cemented paste backfill (CPB) during its development and relate the characteristics of the microstructure to the physical and mechanical properties of CPB. The geometry and morphology of the microstructures of CPB were observed by the scanning electron microscopy (SEM). The characteristics including pore size, pore shape, and orientation of the microstructures of CPB at different curing times were analyzed based on the SEM images. The porosity, fractal dimension, and probability entropy were characterized using the Particles and Pore Recognition and Analysis System (PPRAS). It was found that the pore size, pore shape, and orientation of the microstructure of CPB significantly change as the curing time increases, resulting in the increase of UCS. Meanwhile, the arrangement of the pores affects the mechanical properties of CPB. At the early age of CPB development, the probability entropy is above 0.96, indicating a chaotic pore distribution and no obvious orientation. At the late age of CPB development, the probability entropy becomes smaller and the order and orientation of the pore distribution are enhanced, leading to an increase in USC. The UCS of CPB is also greatly affected by the characteristics of the pore morphology. During the development of CPB, the pore shape becomes smoother. The UCS of CPB approximately linearly improves with an increase in the average roundness of pores.